50.1k views
1 vote
I have a mathematical sequence question a picture included this is an arithmetic sequence

I have a mathematical sequence question a picture included this is an arithmetic sequence-example-1
User Toshiko
by
5.5k points

1 Answer

4 votes

Given the sum:


-4+-3+-2+...+(-5+1n)

This can be expressed using the sum operator:


\sum_{k\mathop{=}1}^n(-5+1k)=-4+-3+-2+...+(-5+1n)

From the left side:


\sum_{k\mathop{=}1}^n(-5+1k)=\sum_{k\mathop{=}1}^n(-5)+\sum_{k\mathop{=}1}^n(1k)

It is well known that:


\begin{gathered} \sum_{k\mathop{=}1}^n(-5)=-5n \\ \\ \sum_{k\mathop{=}1}^n(1k)=(n(n+1))/(2) \end{gathered}

Finally, using these results, we have:


\begin{gathered} \sum_{k\mathop{=}1}^n(-5+1k)=-5n+(n(n+1))/(2)=(-10n+n^2+n)/(2) \\ \\ \therefore\sum_{k\mathop{=}1}^n(-5+1k)=(n(n-9))/(2) \end{gathered}

User Stakolee
by
5.6k points